2018
DOI: 10.1177/1471301218759836
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with informant-reported cognitive decline in older adults: A systemised literature review

Abstract: Background Dementia diagnoses are typically made where there is a significant, progressive decline in cognitive functioning. Evidence of such decline is increasingly established through information provided by informants. However, some studies demonstrate that informant reports may not always be accurate and may be biased by extraneous factors. This review aimed to elucidate factors that have been identified as potentially having some influence on informant reports of cognitive decline. Method A search of Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Additional implications also arise when questionnaires are filled out on behalf of another individual. There are questions regarding the reliability of informant-reported measures as the information being reported has the potential to be influenced by characteristics of both the patient and the informant (Farias, Mungas, & Jagust, 2005;Kemp et al, 2002;Morrell, Camic, & Genis, 2019). Most critically, Mograbi et al's (2012) behavioral assessment of affective empathy examined participants' empathic responses to emotional information.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Additional implications also arise when questionnaires are filled out on behalf of another individual. There are questions regarding the reliability of informant-reported measures as the information being reported has the potential to be influenced by characteristics of both the patient and the informant (Farias, Mungas, & Jagust, 2005;Kemp et al, 2002;Morrell, Camic, & Genis, 2019). Most critically, Mograbi et al's (2012) behavioral assessment of affective empathy examined participants' empathic responses to emotional information.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Regardless of relationship type (spouse, adult child, or friend/other relative), the proxies could make fair estimations about their relatives’ ET use. Even though the present study did not seek to compare different kinds of relationships, other studies have investigated such parameters and found that the kinds of relationships between the PwCIs and the proxies might have an effect on the outcome (Morrell et al., 2019). Spouse proxies have, for example, been shown to score ‘quality of life’ higher than other proxies such as adult children (Lin et al., 2017), which may indicate that the participant–proxy relationship can affect the results in studies of PwCIs.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, providers may rely on informantparticularly family member/close friendreports of patient functioning and decline as a primary source of information (Potter et al, 2009). However, informant reports may be influenced by the informant's perceived caregiver burden or own psychological symptoms (e.g., depression, anxiety; Kudlicka, Clare, & Hindle, 2011;Morrell et al, 2019), which calls into question the accuracy of their reports. Moreover, other factors, such as patient mood and disease severity, may also impact informant reports of cognition (Morrell, Camic, & Genis, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, informant reports may be influenced by the informant's perceived caregiver burden or own psychological symptoms (e.g., depression, anxiety; Kudlicka, Clare, & Hindle, 2011;Morrell et al, 2019), which calls into question the accuracy of their reports. Moreover, other factors, such as patient mood and disease severity, may also impact informant reports of cognition (Morrell, Camic, & Genis, 2019). Therefore, evaluating the concordance of informant-based measures and objective cognitive functioning controlling for relevant factors is essential for the clinical care of PD patients.…”
Section: Introductionmentioning
confidence: 99%